Evidence for a Relatively Warm Mid‐to Late Holocene on the Southeastern Tibetan Plateau - Xiaoping Feng; Cheng Zhao; William J. D'Andrea; Juzhi Hou; Xiangdong Yang; Xiayun Xiao; Ji Shen; Yanwu Duan; Fahu Chen (Geophysical Research Letters)
Abstract The Holocene temperature discrepancy between paleoclimate reconstructions and climate model simulations—known as the Holocene temperature conundrum—calls for new high‐quality Holocene temperature records at high elevations. Here, we present a quantitative Holocene mean annual air temperature record based on a site‐specific branched glycerol dialkyl glycerol tetraethers calibration from a small remote alpine lake on the southeastern Tibetan Plateau. The record reveals a temperature history comprising a relatively cool early Holocene (before 7 ka) followed by a warmer mid‐ to late‐Holocene (after 7 ka), which was likely linked to increasing local annual insolation and greenhouse gases. Three cold events punctuated the general warming trend ca. 10.4 ka, 3.7 ka, and 1.7 ka BP, and correspond closely in time to ice rafting events in the North Atlantic, and to episodes of volcanism and/or unusual solar activity. The entire Holocene temperatures are cooler than the previously identified anthropogenic warming from 1990–2015 AD.